Influence of allelic polymorphism in the 3’ untranslated region of the StTCP23 gene on the tolerance of potato cultivars to the potato spindle tuber viroid - N. V. Mironenko; A. V. Kochetov; O. S. Afanasenko (Труды по прикладной ботанике, генетике и селекции)
Background. It is known that the pathological phenotype of potato plants can be mediated by complementary interactions between the genomic RNA of PSTVd and mRNA of some regulatory genes, which consequently lead to RNA interference, the synthesis of small interfering RNAs (vd-sRNA PSTVd), and impaired morphogenesis. At the same time, symptoms caused by the viroid may vary in different potato cultivars. Here we predict the interactions between the 3’ UTRs of various alleles of the StTCP23 transcription factor gene and the complementary regions in PSTVd genomic RNA.Materials and methods. We selected eight commercial potato cultivars with different symptoms of viroid infection and disease. For each cultivar, six clones of each cDNA amplicon of StTCP23 with a 3’ UTR were identified, and the allelic compositions of the target regions within their 3’ UTRs were characterized.Results. In total, 11 types of alleles of the 3’ UTR StTCP23 segment complementary to the vd-sRNA PSTVd were identified. Cultivars with the A allele (‘Gala’, ‘Colomba’, ‘Favorit’, and ‘Fioletovy’) identical to the reference genome or a high dose of the C allele with a deletion of four nucleotides (cv. ‘Impala’) were characterized by high susceptibility already at the primary (firstyear) infection with the PSTVd. Cvs. ‘Krepysh’, ‘Labadia’ and ‘Riviera’, classified as tolerant during primary inoculation, on the contrary, were characterized by the absence of the A allele and the presence of cultivar-specific mutant alleles.Conclusion. A high degree of polymorphism in the target site (3’ UTR region) of StTCP23 indicates a possible selection pressure on this locus. It can be assumed that cultivars with shorter alleles, which have fewer bases complementary to vd-sRNA in hypothetical duplexes and therefore less likely to induce target gene silencing, are more tolerant to the PSTVd upon primary viroid infection.